2004
DOI: 10.1097/00004872-200405000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy and fibrosis in chronic l-NAME-treated AT2 receptor-deficient mice

Abstract: The AT2 receptor is not essential for development of L-NAME-induced cardiac hypertrophy, fibrosis and concomitant changes in left ventricular performance. In contrast, the AT2 receptor offers a protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…To further document cardiac hypertrophy, we performed morphometric analyses by counting the number of cardiomyocyte nuclei per surface of heart section and by measuring cardiomyocyte cross-sectional areas. 19,20 The 2 quantifications confirmed that Ang II infusion induced a stronger hypertrophy in WT mice than in CalpTG mice (Figure 4b and 4c).…”
Section: Ang Ii-dependent Cardiovascular Hypertrophy In Wt and Calptgsupporting
confidence: 54%
“…To further document cardiac hypertrophy, we performed morphometric analyses by counting the number of cardiomyocyte nuclei per surface of heart section and by measuring cardiomyocyte cross-sectional areas. 19,20 The 2 quantifications confirmed that Ang II infusion induced a stronger hypertrophy in WT mice than in CalpTG mice (Figure 4b and 4c).…”
Section: Ang Ii-dependent Cardiovascular Hypertrophy In Wt and Calptgsupporting
confidence: 54%
“…Cardiac fibrosis is one of the classic features of hypertrophy and is characterized by the expansion of the extracellular matrix attributed to the accumulation of collagen, especially collagen I and connective tissue growth factor. 20,21 It is important to understand the mechanism that stimulates collagen deposition in the heart and to identify approaches to block these processes. One of the findings of this study revealed that Lmcd1 augments cardiac fibrosis and promotes expression of several fibrotic mediators mediated by pressure overload.…”
Section: Bian Et Al Lmcd1 Mediates Cardiac Hypertrophy 261mentioning
confidence: 99%
“…22,23 Calcineurin dephosphorylates NFATs in response to increased intracellular calcium and regulates gene expression in a variety of calcium-sensitive tissues, such as brain, muscle, and lymphocytes. 21,22 Transcriptional activity of NFATs depends on dephosphorylation by calcineurin, which leads to nuclear translocation. [23][24][25] Recent studies revealed that muscle LIM protein directly associates with calcineurin, and this interaction is critical for calcineurin-NFAT signaling.…”
Section: Bian Et Al Lmcd1 Mediates Cardiac Hypertrophy 261mentioning
confidence: 99%
“…Briefly, a telemetry probe catheter (TA11-PA40; Data Sciences International) was inserted into the surgically exposed carotid artery. 23 After surgery, all mice were allowed at least 7 days to recover. Before Ang II/L-NAME treatment, baseline values were continuously recorded for 3 days and averaged.…”
Section: Telemetric Mean Arterial Pressure Measurementsmentioning
confidence: 99%